Implementasi PJBL dengan Mengintegrasikan Konsep Ecogreen dan Ecoenzyme di Lembaga Pendidikan Anak Usia Dini - Riris wardatul adinda; Ratnasari Dwi Ade Chandra; Selasi Priatiningsih (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
The purpose of this study is to investigate how the PJBL model, in conjunction with the Ecogreen and Ecoenzyme ideas, is implemented at Miftahul Ulum Kindergarten and how it affects the development of early NIN environmental consciousness.  The research employed a descriptive qualitative methodology, gathering data through documentation, in-depth interviews, and observation.  According to the study's findings, PJBL based on Ecogreen and Ecoenzyme can boost kids' active participation in educational tasks like recycling, planting plants, and turning organic waste into Ecoenzyme.  A crucial component of this investigation is the separation of organic and non-organic garbage.  While non-organic trash (plastic, metal, and paper) needs special processing through recycling or reduced use, organic waste—such as food scraps, leaves, or fruit peels—is biodegradable and can be converted into compost or ecoenzyme.  Through direct sensory exercises, such as classifying waste according to texture, color, and odor, children are encouraged to comprehend the basic distinctions between the two forms of waste within the context of learning. This enhances conceptual understanding and fosters the development of sustainable habits.  The primary obstacle to PJBL implementation is the requirement for sufficient infrastructure, facilities, and teacher preparation.  All things considered, the PJBL model combined with Ecogreen and Ecoenzyme works well to foster environmental consciousness and critical life skills in young children.